Chromosome-level assembly and gene annotation of Decapterus maruadsi genome using Nanopore and Hi-C technologies - Longyu Chen; Zhixiong Zhou; Zhiyin Zhou; Junyi Yang; Yacheng Deng; Yulin Bai; Fei Pu; Tao Zhou; Peng Xu (Scientific Data, 2024)
Abstract Decapterus maruadsi is one of the representative offshore fish in the Western Pacific. Since the last century, it has become a commercially valuable marine fishery species in the Western Pacific region. Despite its high economic value, there is still a lack of high-quality reference genome of D. maruadsi in germplasm resource evaluation research. Here we report a chromosome-level reference genome of D. maruadsi based on Nanopore sequencing and Hi-C technologies. The whole genome was assembled through 169 contigs with a total length of 723.69 Mb and a contig N50 length of 24.67 Mb. By chromosome scaffolding, 23 chromosomes with a total length of 713.58 Mb were constructed. In addition, a total of 199.49 Mb repetitive elements, 33,515 protein-coding genes, and 6,431 ncRNAs were annotated in the reference genome. This reference genome of D. maruadsi will provide a solid theoretical basis not only for the subsequent development of genomic resources of D. maruadsi but also for the formulation of policies related to the protection of D. maruadsi.